The Clinical Frailty Scale as a triage tool for ICU admission of dialysis patients with COVID-19: an ERACODA analysis. Issue 11 (24th August 2022) - Bouwmans, Pim; Brandts, Lloyd; Hilbrands, Luuk B; Duivenvoorden, Raphaël; Vart, Priya; Franssen, Casper F M; Covic, Adrian; Islam, Mahmud; Rabaté, Clémentine; Jager, Kitty J; Noordzij, Marlies; Gansevoort, Ron T; et al.
Abstract: Background: Several guidelines recommend using the Clinical Frailty Scale (CFS) for triage of critically ill coronavirus disease 2019 (COVID-19) patients. This study evaluates the impact of CFS on intensive care unit (ICU) admission rate and hospital and ICU mortality rates in hospitalized dialysis patients with COVID-19. Methods: We analysed data of dialysis patients diagnosed with COVID-19 from the European Renal Association COVID-19 Database. The primary outcome was ICU admission rate and secondary outcomes were hospital and ICU mortality until 3 months after COVID-19 diagnosis. Cox regression analyses were performed to assess associations between CFS and outcomes. Results: A total of 1501 dialysis patients were hospitalized due to COVID-19, of whom 219 (15%) were admitted to an ICU. The ICU admission rate was lowest (5%) in patients >75 years of age with a CFS of 7–9 and highest (27%) in patients 65–75 years of age with a CFS of 5. A CFS of 7–9 was associated with a lower ICU admission rate than a CFS of 1–3 [relative risk 0.49 (95% confidence interval 0.27–0.87)]. Overall, mortality at 3 months was 34% in hospitalized patients, 65% in ICU-admitted patients and highest in patients >75 years of age with a CFS of 7–9 (69%). Only 9% of patients with a CFS ≥6 survived after ICU admission. After adjustment for age and sex, each CFS category ≥4 was associated with higher hospital and ICU mortality compared with a CFS of 1–3. Conclusions: Frail dialysis patients with COVID-19 were less frequently admitted to the ICU. Large differences in mortality rates between fit and frail patients suggest that the CFS may be a useful complementary triage tool for ICU admission in dialysis patients with COVID-19. Graphical Abstract: